Characteristics of Metroxylon sagu Resistant Starch Type III as Prebiotic Substance - Napisah, Hussin; Rosma, Ahmad; Tan, Zi-Ni (2015)
Resistant starch type III (RS3 ) was produced from sago (Metroxylon sagu) and evaluated for its characteristics as a prebiotic. Two RS3 samples designated sago RS and HCl-sago RS contained 35.71% and 68.30% RS, respectively, were subjected to hydrolyses by gastric juice and digestive enzymes and to absorption. Both sago RS and HCl-sago RS were resistant to 180 min hydrolysis by gastric acidity at pH 1 to 4 with less than 0.85% hydrolyzed. Both samples were also resistant toward hydrolysis by gastrointestinal tract enzymes and intestinal absorption with 96.75% and 98.69% of RS3 were recovered respectively after 3.5 h digestion and overnight dialysis at 37 °C. Sago RS3 supported the growth of both beneficial (lactobacilli and Bifidobacteria) and pathogenic microbes (Escherichia coli, Campylobacter coli, and Clostridium perfringens) in the range of 2.60 to 3.91 log10 CFU/mL. Hence, prebiotic activity score was applied to describe the extent to which sago RS3 supports selective growth of the lactobacilli and bifidobacteria strains over pathogenic bacteria. The highest scores were obtained from Bifidobacterium sp. FTDC8943 grown on sago RS (+0.26) and HCl-sago RS (+0.24) followed by L. bulgaricus FTDC1511 grown on sago RS (+0.21). The findings had suggested that sago RS3 has the prebiotic partial characteristics and it is suggested to further assess the suitability of sago RS3 as a prebiotic material.